Application of drainage technology for L-shaped coalbed methane horizontal well in Southern Qinshui Basin - Yu GAO; Cong ZHANG; Liping ZHAO; Huimin JIA; Mengfu QIN; Wensheng ZHANG; Yanbo JI; Shuai YUAN (Meitan kexue jishu)
As L-shaped horizontal wells have become the main well type for Coalbed Methane (CBM) development, the traditional CBM wells’ drainage technologies can no longer meet the drainage requirements. In order to develop a series of drainage technologies applicable to L-shaped horizontal wells, this article, based on the drainage practices of L-shaped horizontal wells in the Mabi Cooperative Block in Southern Qinshui Basin, analyzes the working principles, process improvements, and technological adaptability to L-shaped horizontal wells of two types of rod-pumping drainage technologies and three types of rodless-pumping drainage technologies. It also studies the relevant supporting processes for sand control and gas prevention, and forms a systematic horizontal well production technology. The results show that: ① Through the optimization of the string structure and the pump structure, the eccentric wear between the rods and the pipes of the two types of rod-pumping drainage technologies can be effectively reduced, which can adapt to the drainage of L-shaped horizontal wells. For the oil pumping unit process, the eccentric wear can be alleviated by installing centralizers optimize the string structure and using a long plunger tubing pump with double fixed valves to improve the adaptability to solid particles. For the top drive screw pump process, by installing spring centralizers differently at different parts of the string structure, using thickened tubing, and installing a deflector and double protect collars at the positions with large dogleg degrees, the eccentric wear can be reduced. ② Rodless processes such as rodless tubing pumps, jet pumps, and electric submersible screw pumps essentially eliminate the problem of eccentric wear between the rods and the pipes, and have a much stronger adaptability to L-shaped horizontal wells than rod-pumping drainage technologies. Jet pumps have the strongest adaptability to solid particles. The maximum displacement of electric submersible screw pumps can reach 50−60 m3/d, the maximum displacement of rodless tubing pumps is generally 20−30 m3/d, and the maximum displacement of jet pumps is generally 30−40 m3/d. ③ The three supporting processes proposed in this article, namely, the graded pump setting process, gas-liquid separation process, and circulating well cleaning process, can effectively reduce the influence from sand particles and CBM gas, and improve the adaptability of the main processes. Among them, the graded pump setting process is that the pump setting position is designed at the well deviation of 65°−75°in the early stage of production to reserve sufficient sand settling space,while the pump setting position is further lowered to fully release the productivity of a single well,in the later stage of production, when the sand production decreases.The circulating well cleaning process improves the sand carrying capacity by injecting water to increase the production rate in the later stage of production. The gravity separation gas anchor can effectively realize gas-liquid separation and reduce the impact of gas channeling on the pump efficiency. After the above process technologies are applied in the study area, they can meet the production requirements of horizontal CBM wells in the middle-deep layer with a burial depth of 1500 m. The average pump inspection cycle of L-shaped horizontal wells has been extended from 265 days to 335 days, and the pump inspection rate in the first year of production has decreased from 29.9% to 19.8%, achieving stable and efficient production of L-shaped horizontal wells.